Coregonus sardinella Valenciennes 1848 - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Coregonus sardinella Valenciennes, 1848. Least Cisco . To 47 cm (18.3 in) TL (Page and Burr 1991). Bering Strait and Siberia west to White Sea; Arctic coasts of Alaska east to Rasmussen Basin and Chantrey Inlet, King William Island, Nunuvut (Reist in Coad and Reist 2018) [records further east are without documentation—Reist in Coad and Reist 2018] and south to Bristol Bay, Bering Sea (Mecklenburg et al. 2002). Coastal waters near shore and fresh water. Anadromous and landlocked populations (Mecklenburg et al. 2002). Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 53, DOI:10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008